Interpersonal Communication and Teacher Attention to Learning Interests of Elementary Students - Saputri, Ayu Amelli; Jefryadi, Jefryadi; Putra, Bramana Nanditya (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the influence of interpersonal communication and teacher attention on students' learning interest in Madrasah Ibtidaiyah. The research approach used is quantitative with descriptive correlational method. The study population consisted of 150 students in grades I-III at MI in Pagar Alam area, with a sample of 109 students selected through simple random sampling technique. Data were collected using a closed questionnaire with a Likert scale of 1-4 which has been tested for validity and reliability. The results of the study indicate that teacher interpersonal communication is in the high category (mean = 3.42), teacher attention is in the high category (mean = 3.45), and student learning interest is in the high category (mean = 3.3). Based on multiple linear regression analysis, the equation Y = 1.12 + 0.41X1 + 0.37X2 is obtained. The results of the partial test show that teacher interpersonal communication has a significant effect on learning interest (t-hit = 4.812, sig. 0.000), as well as teacher attention (t-hit = 4.209, sig. 0.000). Simultaneous tests prove that both variables together have a significant effect on learning interest (F-hit = 42.51, sig. 0.000) with a coefficient of determination of 59.3%. The conclusion of this study confirms that interpersonal communication and teacher attention are important determinants in fostering learning interest in Madrasah Ibtidaiyah students. The practical implications of this study emphasize the importance of developing interpersonal communication competencies and the ability to provide sincere attention for teachers in creating a conducive and motivating learning environment.